Descrição e classificação das expressões cristalizadas com ser e estar do português do Brasil - Carneiro, Amanda dos Santos (Universidade Federal de São Carlos, 2016)
This dissertation aims to make a description and classification of frozen expressions of Brazillian's Portuguese that are built with the verbs ser and estar. We consider that frozen expressions are those whose overall meaning cannot be calculated from the sum of the parts that make it up, for example, pé frio in the phrase Leo é pé frio. For this work was adopted the theoretical-methodological perspective of Lexicon-Grammar (GROSS, 1975; GROSS 1981), which is fundamentally based on the Zellig Harris’s transformational grammar (1976). We have analyzed 530 expressions which are divided into eight different classes as distributional regularities. Each class is described in binary tables in which the lines are the expressions and the columns are the syntactic-semantic properties of each input. From the analysis of these classes, we can see a number of regularities showing that such predicates are not an anomaly of the langue. This classification proves helpful also to the Natural Language processing, since the binary tables may be adapted so that computer programs to interpret both the syntactic and semantically correct shape to use as the new searches in corpora.
Keywords: Léxico-gramática; Expressão cristalizada; Adjetivo; Ser; Estar; Frozen expressions; Lexicon-grammar; LINGUISTICA, LETRAS E ARTES::LINGUISTICA